Predictive Factors of Hemorrhage After Thrombolysis in Patients With Acute Ischemic Stroke - Sun, Fan; Liu, Heng; Fu, Hui-xiao; Li, Cheng-bo; Geng, Xiao-jing; Zhang, Xiao-xuan; Zhu, Jiang; Ma, Zheng; Gao, Yan-jun; Dou, Zhi-jie (Frontiers in Neurology, 2020)
Background: Ischemic stroke has a poor prognosis and brings a ponderous burden on families and society. Hemorrhagic transformation (HT) after intravenous thrombolysis can increase the mortality of patients with ischemic stroke. Thus, finding new HT biomarkers to be applicable in clinical practice is of great importance. Methods: The related risk factors were recruited for analysis, including smoking, drinking, hyperlipidemia, diabetes, anamnesis and pathological indicators. Moreover, the relationship between serum levels of caveolin-1, caveolin-2 and HT after rt-PA treatment were also studied. Results: We studied 306 patients with acute ischemic stroke treated with recombinant tissue type plasminogen activator (rt-PA) within 4.5 h of symptom onset. The results showed that Age ≥68 years, smoking, Atrial fibrillation, NIHSS score before thrombolysis ≥17, and systolic pressure 2 h after thrombolysis (mmHg) ≥149 increased the risks of HT after rt-PA administration. Remarkably, the concentration of caveolin-1 (ng/mL) ≤0.12 and caveolin-2 (ng/mL) ≤0.43 in serum increased the risks of HT after rt-PA administration. Conclusion: Knowledge on the risk factors associated with HT after rt-PA treatment may help develop treatment strategies and reduce the risk of HT. Caveolin-1 and caveolin-2 can be predictors of HT after rt-PA administration. These findings provide evidence for future further investigations aimed to validate these biomarkers.